2008
DOI: 10.1021/ie800374h
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Mixture Vapor−Liquid Equilibria with the SPEADMD Model

Abstract: The present work examines the accuracy of the SPEADMD molecular simulation methodology in correlating experimental data relative to a standard low-pressure database for testing VLE models. The database contains 104 binary systems categorized according to polarity and ideality. Although the database is somewhat small, it covers a broad range of chemical functionality, including halocarbons and carboxylic acids as well as hydrocarbons and alcohols. Six models were tested and compared for their characterization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Gray and Elliott 12 presented results for mixtures over a limited range of size ratios, but these were never published. These results were summarized by Vahid et al 13 An apparent inconsistency was observed by Vahid et al when the trend was analyzed in the long chain limit. 13 That inconsistency has now been found to be unrelated to the entropy of mixing.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Gray and Elliott 12 presented results for mixtures over a limited range of size ratios, but these were never published. These results were summarized by Vahid et al 13 An apparent inconsistency was observed by Vahid et al when the trend was analyzed in the long chain limit. 13 That inconsistency has now been found to be unrelated to the entropy of mixing.…”
Section: Introductionmentioning
confidence: 92%
“…These results were summarized by Vahid et al 13 An apparent inconsistency was observed by Vahid et al when the trend was analyzed in the long chain limit. 13 That inconsistency has now been found to be unrelated to the entropy of mixing.…”
Section: Introductionmentioning
confidence: 92%
“…Event-Driven Particle-Dynamics (EDPD) is the oldest particle simulation technique [1] and has found application in a wide range of fields, from predicting vapor-liquid equilibria [7] to the design of granular vibration dampers [3]. Although typically used to simulate simple particle models such as the hard-sphere, the EDPD technique remains a general approach to particle simulations as potentials can be discretized to accurately approximate more conventional model systems, such as Lennard-Jonesium [6], or directly fit to physical data [37]. Introducing the coefficient of restitution, EDPD algorithms can also be used to simulate systems of dissipatively interacting particles, such as granular flows.…”
Section: Introductionmentioning
confidence: 99%
“…the EDPD technique remains a general approach to particle simulations as potentials can be discretized to accurately approximate more conventional model systems, such as Lennard-Jonesium [6], or directly fit to physical data [37]. Introducing the coefficient of restitution, EDPD algorithms can also be used to simulate systems of dissipatively interacting particles, such as granular flows.…”
mentioning
confidence: 99%
“…It is only relatively recently that fine-tuned discrete potentials for detailed, atomistic simulations have started to appear; these include force fields for a broad range of compounds, including hydrocarbons 14 and fluorocarbons 15 , organic acids 16 , esters, ketones and other organic compounds 17,18 , phospholipids 19 , and peptides and proteins 20 . The use of TPT has even allowed rapid and direct fitting of discrete potentials to experimental data 14,21,22 .…”
Section: Introductionmentioning
confidence: 99%